Human β-Defensin 23 as a Carrier for In Vitro and In Vivo Delivery of mRNA - Kim Kyoung-Ran; Kim Junghyun; Cho, Seunghye; Ahn, Dae-Ro (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The successful application of mRNA therapeutics hinges on the effective intracellular delivery of mRNA both in vitro and in vivo. However, this remains a formidable challenge due to the polyanionic nature, longitudinal shape, and low nuclease resistance of mRNA. In this study, we introduce a novel mRNA delivery platform utilizing a human β-defensin peptide, hBD23. The positive charge of hBD23 allows it to form nanocomplexes with mRNA, facilitating cellular uptake and providing protection against serum nucleases. When optimized for peptide-to-mRNA (N/P) ratios, these hBD23/mRNA complexes demonstrated efficient cellular delivery and subsequent protein expression both in vitro and in vivo. Importantly, as hBD23 is human derived, the complexes exhibited minimal cytotoxicity and immunogenicity. Given its high biocompatibility and delivery efficiency, hBD23 represents a promising platform for the in vitro and in vivo delivery of mRNA.